Perjanjian Sewa Menyewa Tanah Adat di Desa Serangan Denpasar Selatan - I Putu Elvin Mahendra; I Made Suwitra; I Ketut Sukadana (Jurnal Preferensi Hukum, 2020)
The position of the Customary Village as a customary legal alliance, has the authority and obligation to control, regulate and manage all the land belonging to the Customary Village within the Customary Village area as customary rights. In entering into an agreement to lease customary land with another party, Desa Adat has the right to land in terms of granting permits based on agreements made by both parties. Agreements that have been agreed should be accountable so as not to lead to defaults in the future. The method used in this research is the empirical method, by reviewing the statutory procedures that apply in making lease agreements for customary land and using a sociological problem approach to social law relating to legal norms both in legislation and in awig-awig. In PERDA Number 4 of 2019 concerning Customary Villages in Bali regulates the duties and authority of the Customary Villagers in maintaining the economy of the village, so that they are authorized to carry out legal actions (agreements) especially lease agreements for customary land provided they have fulfilled the requirements of the shah. An agreement can be regulated in article 1320 Civil Code. Whereas regarding the application of sanctions for parties who defaulted in the lease agreement on customary land, it was given to those who violated the agreement based on the agreement of the village paruman. Where the sanctions can be resolved based on positive law in Indonesia, namely through the judicial process.